Evaluation of bone regeneration in extracted tooth sockets using simvastatin - A split-mouth study - Abhishek Deshpande; Vijaylaxmi Shettar; S M Kotrashetti; Divyank Tiwary (Wolters Kluwer Medknow Publications, 2023)
Introduction: Tooth extraction is followed by alveolar bone resorption, making rehabilitation difficult. Various materials such as autografts and xenografts have been used, but they have their own limitations. Studies have showed that "Statins" like simvastatin used for lowering cholesterol levels also increase the expression of bone morphogenetic protein 2 which has an important role in osteoblast differentiation and mineralization. This facilitates the further rehabilitation of the patient after tooth extraction. The study was conducted to evaluate bone regeneration in extracted tooth socket using simvastatin. Materials and Methods: A randomized control trial split-mouth study was done in patients of 18-65 years' age group. A total of 31 patients requiring bilateral extractions were selected without any gender bias. Simvastatin with gelatin sponge was placed in extracted socket on study side and normal extraction done was done on the control side. The patients were followed up for a period of 6 months. The clinical parameters of pain and swelling were assessed on the 1st and 3rd day. The radiographic parameter was assessed on the 1st postextraction day, 1st month, 3rd month, and 6th month subsequently. The data were subjected to the statistical analysis. Results: Pain was assessed using the Visual Analog Scale; swelling was assessed using the paired sample t-test. Initially, pain and swelling more on the study side as compared to control side which subsided later. The bone density was evaluated on the 1st day, 1st month, 3rd month, and 6th month postoperatively using the independent sample t-test. They showed early bone formation on the study side as compared to the control side, which was statistically significant between the study and control groups. Conclusions: Simvastatin can be used in extracted sockets as it causes early bone formation.